2020
DOI: 10.2807/1560-7917.es.2020.25.12.2000256
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the infection and case fatality ratio for coronavirus disease (COVID-19) using age-adjusted data from the outbreak on the Diamond Princess cruise ship, February 2020

Abstract: Adjusting for delay from confirmation to death, we estimated case and infection fatality ratios (CFR, IFR) for coronavirus disease (COVID-19) on the Diamond Princess ship as 2.6% (95% confidence interval (CI): 0.89-6.7) and 1.3% (95% CI: 0.38-3.6), respectively. Comparing deaths on board with expected deaths based on naive CFR estimates from China, we estimated CFR and IFR in China to be 1.2% (95% CI: 0.3-2.7) and 0.6% (95% CI: 0.2-1.3), respectively.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
304
1
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(343 citation statements)
references
References 7 publications
(16 reference statements)
28
304
1
10
Order By: Relevance
“…2D and table S2). Our estimate of overall IFR is similar to other recent studies that found values of between 0.5 and 0.7% for the Chinese epidemic (6)(7)(8). We find men have a consistently higher risk than women of hospitalization (RR 1.25, 95% CrI: 1.22-1.29), ICU admission once hospitalized (RR: 1.61, 95% CrI: 1.56-1.67) and death following hospitalization (RR: 1.47, 95% CrI: 1.42-1.53) ( fig.…”
supporting
confidence: 91%
“…2D and table S2). Our estimate of overall IFR is similar to other recent studies that found values of between 0.5 and 0.7% for the Chinese epidemic (6)(7)(8). We find men have a consistently higher risk than women of hospitalization (RR 1.25, 95% CrI: 1.22-1.29), ICU admission once hospitalized (RR: 1.61, 95% CrI: 1.56-1.67) and death following hospitalization (RR: 1.47, 95% CrI: 1.42-1.53) ( fig.…”
supporting
confidence: 91%
“…These values for the IFR are consistent with the findings in [2] (0.66% in China) and [3] (0.9% in the UK). The value of 1.3% estimated on the Diamond Princess cruise ship [4] falls above the top end of our 95% CI. This reflects the age distribution on the ship, which was skewed towards older individuals (mean age: 58 years), among whom the IFR is higher [3,4].…”
Section: Discussionmentioning
confidence: 41%
“…Based on the PCR-confirmed cases in international residents repatriated from China on January 2020, Verity et al [2] obtained an estimate of the infection fatality ratio (IFR) of 0.66% in China, and, adjusting for non-uniform attack rates by age, an IFR of 0.9% was obtained in the UK [3]. Using data from the quarantined Diamond Princess cruise ship in Japan and correcting for delays between confirmation and death, Russel et al [4] obtained an IFR of 1.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Para identificar diferencias en la letalidad se ha desarrollado un índice de letalidad relativa, utilizando la tasa de letalidad del brote de COVID-19 en el crucero Princess Diamond como referencia 10 . Este índice es la letalidad de cada país en relación con la letalidad que hubo en el crucero.…”
Section: Métodounclassified
“…Además, la mayoría de los casos se detectaron en pacientes nacidos en países de la OCDE 10 , similares a los incluidos en este estudio. Hubo siete muertes, todas en pacientes mayores de 70 años, resultando una tasa de letalidad del 1,01% 10 .…”
Section: Métodounclassified